Determining Optimum Production Quantity on Multi-Product Home Textile Industry by Simulated Annealing - Yuliastuti, Gusti Eka; Rizki, Agung Mustika; Mahmudy, Wayan Firdaus; Tama, Ishardita Pambudi (Journal of Information Technology and Computer Science, 2018)
Production planning is a plan aimed at controlling the quantity of products produced. Production planning is very important to be carried out by the company so that the production will always be controlled. It is very difficult to plan production with a variety of product variations because each product certainly has a different demand value from its customers. This has become a complex problem so an algorithm is needed to overcome these problems. Simulated Annealing can produce optimal solutions more effectively and efficiently. Production costs generated by applying Simulated Annealing are Rp. 6,902,406,000, - for all types of products, which is better than existing condition.